2001
DOI: 10.1038/35081058
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale forest girdling shows that current photosynthesis drives soil respiration

Abstract: The respiratory activities of plant roots, of their mycorrhizal fungi and of the free-living microbial heterotrophs (decomposers) in soils are significant components of the global carbon balance, but their relative contributions remain uncertain. To separate mycorrhizal root respiration from heterotrophic respiration in aboreal pine forest, we conducted a large-scale tree-girdling experiment, comprising 9 plots each containing about 120 trees. Tree-girdling involves stripping the stem bark to the depth of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

99
1,321
18
15

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,692 publications
(1,453 citation statements)
references
References 14 publications
99
1,321
18
15
Order By: Relevance
“…obs.). Moose can decrease mycorrhizal colonization in taiga ecosystems through winter browsing of willow and poplar twigs (Rossow et al., 1997), and, furthermore, browse the sites throughout the summer, which would have a greater impact on the flow of photosynthates to roots and, subsequently, mycorrhiza, as ECM fungi are dependent on newly fixed carbon (Ekblad et al., 2013; Högberg et al., 2001). Contrary to our hypothesis, however, we found no correlation between B. pubescens biomass and EMM biomass which could mean that other factors connected to herbivory, such as trampling and fertilization, may have influenced mycelial production, although no correlation to any of the measured soil variables corroborated a fertilization effect either.…”
Section: Discussionmentioning
confidence: 99%
“…obs.). Moose can decrease mycorrhizal colonization in taiga ecosystems through winter browsing of willow and poplar twigs (Rossow et al., 1997), and, furthermore, browse the sites throughout the summer, which would have a greater impact on the flow of photosynthates to roots and, subsequently, mycorrhiza, as ECM fungi are dependent on newly fixed carbon (Ekblad et al., 2013; Högberg et al., 2001). Contrary to our hypothesis, however, we found no correlation between B. pubescens biomass and EMM biomass which could mean that other factors connected to herbivory, such as trampling and fertilization, may have influenced mycelial production, although no correlation to any of the measured soil variables corroborated a fertilization effect either.…”
Section: Discussionmentioning
confidence: 99%
“…Berthelin (1983) attributed the low pH in the mycorrhizosphere zone to oxidized inorganics (e.g., sulphur) and the production of organic acids (e.g., oxalic, carbonic, citric, acetic) by the activities of ECM. Singh et al (2003) and Högberg et al (2001) reported that respiration from ectomycorrhizal roots is equivalent to up to 65% of total soil respiration. This finding has significant implications with respect to the generation of exudates (e.g., organic acids) that can subsequently lower the pH and further enhance the rates of mineral weathering in ECS compared to N-ECM soils.…”
Section: Chemical Properties Of Ecs and N-ecm Soilsmentioning
confidence: 99%
“…root exudates and sloughed-off root cells; Andrews et al, 1999;Kuzyakov, 2006), consequently these components are usually estimated together (sensu Wiant, 1967) and we henceforth use the term 'rooterhizosphere respiration' to include both autotrophic root respiration and heterotrophic respiration in the rhizosphere. Tree-girdling has been used successfully to estimate rooterhizosphere respiration in a northern Scots pine forest (Högberg et al, 2001) and has the advantage of not changing the abiotic soil environment (Subke et al, 2006), however it has been less successful in studies of tropical trees because of large carbohydrate reserves in the existing root system of some species, which provide C for the maintenance of fine roots when the supply of C from aboveground assimilation is disrupted (Binkley et al, 2006;Nottingham et al unpublished data). Thus, most attempts at estimating rooterhizosphere respiration in tropical and subtropical forests have used either an indirect mass balance approach (e.g.…”
Section: Introductionmentioning
confidence: 99%